Eksplorasi Literasi Matematika Peserta Didik SMP Negeri 1 Pangenan Berdasarkan Tingkat Motivasi Intrinsik: Indonesia - Muhamad Rizki Subarkah; Wardono; Bambang Eko Susilo (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2025)
Mathematical literacy is an essential 21st-century competency. However, national assessment results and international studies such as PISA indicate that Indonesian students’ mathematical literacy remains below the average. A similar condition was found at SMP Negeri 1 Pangenan, where this research was conducted. Based on an intrinsic motivation questionnaire administered to 34 students, their motivation levels were classified into three categories: high (), medium (), and low (). This study aims to explore students’ mathematical literacy skills based on their levels of intrinsic motivation. The research employed a qualitative descriptive–exploratory approach. The subjects were selected using purposive sampling, consisting of six eighth-grade students representing each level of intrinsic motivation. Data were collected through intrinsic motivation questionnaires, mathematical literacy tests, semi-structured interviews, classroom observations. Data were analyzed through the stages of data reduction, data display, conclusion drawing. The findings show that: (1) Students with high intrinsic motivation demonstrated excellent performance in almost all components of mathematical literacy, accompanied by strong learning control, self-confidence, and full engagement. (2) Students with medium intrinsic motivation showed fairly good but inconsistent performance, particularly in reasoning, the use of symbols. Their learning control and self-confidence were not yet stable. (3) Students with low intrinsic motivation tended to perform at a fair to low level, with weak motivation and low engagement. These findings indicate that there are clear differences in mathematical literacy performance based on students’ levels of intrinsic motivation. This study recommends implementing learning approaches that take motivational variations into account to optimize students’ mathematical literacy